ERUPTIVE SYRINGOMA IN A FORTUITOUS ASSOCIATION WITH LEPROSY - THE IMPORTANCE OF ACTIVE SEARCH - Filho, Fred Bernardes; Quaresma, Maria Victória; Bianco, Stephanie; Razé, Mariana de Campos; Bussad, Camila Sanches; da Silva, Gisele Reis Cunha; Alves, Andreia Oliveira; Nery, José Augusto da Costa (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
The metropolitan area of Rio de Janeiro concentrates the most of new cases of leprosy, suggesting a relationship between high detection rates with higher population density and larger numbers of decentralized health units. For improved access to diagnosis and treatment is necessary training in disease. The authors present a case with casual link between leprosy and eruptive syringoma showing a representation of an endemic area.